Application of Machine Learning in Ethnomusicology Education under the Belt and Road Initiative - Abu Bakar Modh Sheikh; Rong Li (Research Synergy Foundation, 2025)
The integration of machine learning has transformed the landscape of music education. To address the challenges of assessment accuracy and personalized instruction in ethnic music education along the